2021
DOI: 10.14407/jrpr.2021.00171
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dose Rates from Four Surveys around the Fukushima Daiichi Nuclear Power Plant for Location Factor Evaluation

Abstract: Background: The radionuclides released by the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident 9 years ago are still being monitored by various research teams and the Japanese government. Comparison of different surveys’ results could help evaluate the exposure doses and the mechanism of radiocesium behavior in the urban environment in the area. In this study, we clarified the relationship between land use and temporal changes in the ambient dose rates (air dose rates) using big data.Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…For example, TEPCO employees were not only working in nondecontaminated residential areas, but also on paved roads and house demolition sites. On the paved roads, radioactive cesium may have been washed away by weathering effects [37,38]. The ground under the houses may have been a little contaminated [35].…”
Section: Conversion Coefficient From Air Dose Rates By Airborne Monit...mentioning
confidence: 99%
“…For example, TEPCO employees were not only working in nondecontaminated residential areas, but also on paved roads and house demolition sites. On the paved roads, radioactive cesium may have been washed away by weathering effects [37,38]. The ground under the houses may have been a little contaminated [35].…”
Section: Conversion Coefficient From Air Dose Rates By Airborne Monit...mentioning
confidence: 99%
“…In other words, if there is a change in the distribution of radioactive cesium within 30 m, a dose gradient will occur. Previous studies [44][45][46][47]49] have reported that the radiation source distribution was different in each land use situations. So, it is considered that a dose gradient occurs under conditions where different land use conditions were close.…”
Section: Comparison Of Conversion Coefficients Of Each Zone 341 Conve...mentioning
confidence: 93%
“…The previous study and this study results are notably lower than the expected conversion coefficient 0.7. Because approximately 90% of measurements based on airborne radiological monitoring contributed to radiation sources within a 470 m radius range [43], airborne radiological monitoring values tend to have difficulty reflecting decontamination [14,16,37] and weathering effects [44][45][46][47] on the ground. On the other hand, about 90% of ground-based measurements were contributed by radiation sources with a diameter of 100 m [43], so these measurements reflect gradient dose Measurements by airborne radiological monitoring might have been higher than actual due to the topographical effects at mountainous regions [37,48].…”
Section: Comparison Of Conversion Coefficients Of Each Zone 341 Conve...mentioning
confidence: 99%